Organic matter fractions of an Oxisol under influence of sewage sludge doses - Soares, Emanuelle Mercês Barros; Silva, Carlos Alberto; Dias, Bruno de Oliveira; Bettiol, Wagner; Belizário, Maísa Honório (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this work was to evaluate the effect of the continued application of increasing doses of sewage sludge on the contents of carbon (C) associated to the light fraction (LF-C) and to the heavy fraction (sand-C, silt-C and clay-C) of soil organic matter, in Oxisol samples. The experiment was installed in 1999, in Jaguariúna, SP, Brazil. The data were obtained after the sixth sewage sludge (SS) application, and six corn cultivation cycles with accumulated doses (dry base) 0, 30, 60, 120 and 240 Mg ha-1, and the treatments were: control, without sewage sludge addition (LO); application of sewage sludge to furnish one (L1), two (L2), four (L4), and eight (L8) times the N required by corn. As a reference, an adjacent area under forest was also sampled. The increase in the applied sewage sludge doses increases linearly the content of organic C (org C), silt-C and sand-C. As the sewage sludge dose is increased up to 120 Mg ha-1, there is an increase in the content of LF-C. The content of C associated to the evaluated compartments of soil organic matter follows this contribution order: FL-C < sand-C < silt-C < clay-C.